IMPROVING STUDENTS SPEAKING ABILITY BY USING PRESENTATION, PRACTICE, PRODUCTION (PPP) METHOD AT THE SEVENTH GRADE STUDENTS OF SMP NEGERI 2 TELUKDALAM IN 2019/2020 - Lies Dian M. Ndraha (Institut Pendidikan Tapanuli Selatan, 2020)
This research is aimed to improve the students ability in speaking by using Presentation, Practice and Production (PPP) Method at seventh grade of SMP Negeri 2 Teluk dalam in 2019/2020. The population of the seventh grade students the students in SMP Negeri 2 Teluk dalam were 2 classes. The researcher choose VII-A as the subject of this research which consisted of 20 students. Classroom Action Research was used as the research method. This research consisted of two cycles. The procedure of the research consisted of planning, action, observation and reflection. The kind of datum analysis, they were: qualitative data and quantitative data. The result of data analysis show that in cycle I who were 10 students passed and 10 students were failed. The average score was 56,05. After doing reflection, it was continue to cycle II who were 16 students succesful to achieve the MCC and 4 students were unsuccesful. The average score was 71,5. The result of research show that this method was successful to improve the students speaking. The researcher suggest the teacher to teach the students using this method because this method is effective or appropriate to be applied in teaching speaking. For students which felt shy to practice speaking, hoped able to encourage the students to speak well and more active in the classroom. For the next reseacher and the readers, this result can give the contribution conduct further research.